The Impact of Workplace Violence and Work-Related Stress on Employee Performance at PT. Multisarana Gitatama - Fauzia, Vynnie (Journal Research of Social Science, Economics, and Management, 2026)
Workplace violence and job stress are significant factors affecting employee performance. Violence, both verbal and non-verbal, disrupts employees' well-being and productivity, while job stress, stemming from workload, poor conditions, and lack of support, contributes to decreased efficiency and job satisfaction. This study aims to examine the impact of workplace violence and job stress on employee performance at PT. Multisarana Gitatama. A quantitative approach was used, with data collected through surveys from employees. The relationships between workplace violence, job stress, and employee performance were analyzed using multiple linear regression. The findings show that both workplace violence and job stress significantly affect employee performance. Verbal abuse negatively impacts focus and motivation, while job stress reduces overall work efficiency. Interestingly, job stress also serves as a motivator for some employees, highlighting its complex nature. Workplace violence and job stress significantly reduce employee performance. Organizations must address these issues by fostering a supportive environment, implementing stress management strategies, and enforcing policies to prevent and manage violence. Further research is needed to explore these relationships in more depth.